PROFILE OF STUDENTS' PROBLEM-SOLVING ABILITIES BASED ON KEIRSEY'S PERSONALITY IN SOLVING ETHNOMATHEMATICS PROBLEMS: PROFIL KEMAMPUAN PEMECAHAN MASALAH SISWA BERDASARKAN TIPE KEPRIBADIAN KEIRSEY DALAM MEMECAHKAN MASALAH ETNOMATEMATIKA - Nur Agustiani; Isma Nastiti Maharani; Ida Rahmawati (MaPan : Jurnal Matematika dan Pembelajaran, 2024)
Problem-solving abilities are essential for students to face developments in the 21st century. This research examines students' problem-solving abilities in solving ethnomathematics-based problems in terms of Keirsey's personality type. This research uses a qualitative approach with a case study method. The research instrument is a questionnaire to measure Keirsey's personality type (artisan, guardian, idealist, and rational), an ethnomathematics-based problem-solving test instrument with the Polya problem-solving stages. Research subjects were chosen based on specific considerations: students with artisan, guardian, idealist, and rational personality types. Data collection was carried out using questionnaires, tests, and interviews. Based on the results of the analysis, it was found that each student with a different personality type had different problem-solving abilities. Students with a rational personality type can fulfill all stages of Polya problem-solving in each problem. Students with the guardian personality type skip checking back on a problem. Students with an artisan personality type lack planning. Meanwhile, students with an idealistic personality type cannot fulfill the problem-solving stages in all problems. These findings emphasize differences in problem-solving abilities for each personality type, so they can be used as a reference for designing learning based on personality type.